Does mating interfere in the biological characteristics of a population of Trichogramma pretiosum? - PRATISSOLI,DIRCEU (2014)
Trichogramma spp. are parasitoids used in the regulation of insect populations that can cause economic damage. In order to ensure good performance, understanding some of their biological characteristics is essential. The objective of this study is to evaluate whether mating interferes with the biological characteristics of a population of Trichogramma pretiosum collected in the field. In all experiments, groups of mated and unmated females were used. We also verified any interference from mating on the biological characteristics of the offspring. We found that mating can alter the parasitism and longevity of genitor females, in addition to changing longevity among the descendants, but once parasitized, the eggs develop normally, showing similar emergence percentage and number of offspring as those from unmated females. In addition, we verified that the population of T. pretiosum collected in the field presented individuals with reproductive thelytokous and arrhenotokous characteristics. This fact highlights the importance of careful investigation on the reproduction mode of populations collected in the field, thus avoiding problems in the effective management of insect populations.